Polycyanurate thin film optical waveguide for integrated optics applications - SHARMA, SUDHIR KUMAR (2003)
This paper reports on the fabrication and characterization of polymer optical waveguide. The polymer films were used by dip coating technique. Various waveguide parameters such as refractive index, optical losses, thickness of guide has been reported. Polycyanurate synthesized as planar optical waveguide exhibits low optical loss (< 2 dB/cm) having refractive index 1.592 and excellent absorption spectra in the wavelength range (1540-1560 nm) which makes this polymer promising for integrated optical devices.